Buzz Group Technique to Increase Writing Skill at EFL Students of Junior High School in Indonesia (International Journal of Theory and Application in Elementary and Secondary School Education, 2019)
This research aimed to find out whether there was a significant difference of writing skill achievement between EFL students who were taught using Buzz Group technique and those who were taught using a conventional method by expecting the Buzz Group technique improved EFL students’ writing skill achievement at SMP Negeri 7 Baubau, Southeast Sulawesi. Design of this research was a quasi-experimental in which there were 22 students in both control and experimental groups. The findings of this research obtained: 1) the mean score of EFL students’ writing skill at pretest in experimental class was 51.09 in low category and the mean score of posttest was 72.18 in high category; 2) the mean score of EFL students’ writing skill at pretest in control class was 49.82 in low category and the mean score of posttest was 56.36 in moderate category; 3) the score of Asymp. Sig. (2-tailed) from hypothesis test was 0.000 in which it was less than 0.05. Therefore, this research concluded that there was a significant difference between of writing skill achievement between EFL students who were taught using Buzz Group technique and those who were taught using the conventional method at SMP Negeri 7 Baubau. In addition, the use of Buzz Group technique is better than the conventional method to improve EFL students’ writing skill achievement.